SPEECH FUNCTION IN SHORT MESSAGE SERVICE (SMS) BROADCAST ON TELKOMSEL - Iskandar Zulkarnain; Sofia Idawati Lubis; Maswidar Zalukhu (English Education Study Program FKIP Universitas Alwashliyah Medan, 2021)
This study discussed the speech function in SMS broadcast. The objective of the study was to find out the types of speech function and the dominant type used in SMS broadcast. The method used in this study was descriptive qualitative design. The sources of the data were taken randomly from the SMS broadcast in TELKOMSEL collected from December 2018 until May 2019 and there were 25 SMS broadcast. The data were classified based on the types of speech function. Based on the findings, it was found that they were 58 speech function occurred such as Command (19 or 32.76%), Statement (25 or 43.10%), Question (2 or 3.45%), and Offer (12 or 20.69%). The most dominant type of speech function was Statement. This result showed that the most dominant type occurred type was due to the fact that the provider (TELKOMSEL) should deal with the customers’ demand to provide them goods or services or the customers should follow the program provided by the service provider.